2013
DOI: 10.1097/mco.0b013e32835a8842
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle protein metabolism in human heart failure

Abstract: Purpose of review This review considers evidence that the clinical condition of heart failure (HF) alters skeletal muscle protein synthesis and/or breakdown to promote skeletal muscle wasting and functional decrements that ultimately contribute to the symptomology of the disease. Recent findings Advanced heart failure is frequently accompanied by muscle atrophy and a cachectic phenotype. Protein metabolic derangements that promote this phenotype are understudied and poorly understood. Instead, most investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…17 As can be seen from the previous section, skeletal muscle wasting can be both a cause or a consequence of cachexia. 26 Increased catabolism and body weight loss are also associated with a decrease in respiratory muscle strength. 73 It was recently observed that fat mass wasting is also predictive of adverse outcome.…”
Section: Clinical Consequences Of Cachexiamentioning
confidence: 99%
See 4 more Smart Citations
“…17 As can be seen from the previous section, skeletal muscle wasting can be both a cause or a consequence of cachexia. 26 Increased catabolism and body weight loss are also associated with a decrease in respiratory muscle strength. 73 It was recently observed that fat mass wasting is also predictive of adverse outcome.…”
Section: Clinical Consequences Of Cachexiamentioning
confidence: 99%
“…As anabolic pathways are probably insufficient to recover muscle size and function to prehospitalization levels, efforts to prevent disease exacerbation should be emphasized. 26 Finally, it has been showed that increased catabolism not only occurs in skeletal muscle but also in adipose tissue.…”
Section: Imbalance Between Anabolic and Catabolic Processesmentioning
confidence: 99%
See 3 more Smart Citations